2020
DOI: 10.3389/fendo.2020.00427
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of IVF/ICSI-FET Outcomes in Women With Advanced Endometriosis: Influence on Ovarian Response and Oocyte Competence

Abstract: Aims: To determine the impact of advanced endometriosis (EMS) on in vitro fertilization/intracytoplasmic sperm injection and frozen–thawed embryo transfer (IVF/ICSI-FET) outcomes and analyze the influencing factors. Methods: A retrospective study was conducted on sterile women with ovarian endometriomas (OMAs), including patients who underwent laparoscopic cystectomy ( n = 224, 224 IVF/ICSI cycles, 205 FET cycles) and aspiration (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 56 publications
6
25
0
Order By: Relevance
“…However, the influence of endometrioma per se on ART outcomes is still undetermined. ART results vary by report, with some showing decreased numbers of oocytes retrieved and poor embryo quality, and other results present identical live birth rates as in patients without endometrioma despite fewer oocytes retrieved during IVF treatment ( 16 ). Previous studies have mostly focused on the effect of surgical removal of endometrioma on ART outcomes rather than the effect of the endometrioma itself or have included a single-endometrioma group without a matching control group for comparison ( 17 , 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the influence of endometrioma per se on ART outcomes is still undetermined. ART results vary by report, with some showing decreased numbers of oocytes retrieved and poor embryo quality, and other results present identical live birth rates as in patients without endometrioma despite fewer oocytes retrieved during IVF treatment ( 16 ). Previous studies have mostly focused on the effect of surgical removal of endometrioma on ART outcomes rather than the effect of the endometrioma itself or have included a single-endometrioma group without a matching control group for comparison ( 17 , 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, an increased dose of FSH did not improve cumulative live birth rates compared with a standard dose ( 40 ). Li et al found that the AFC was an independent factor associated with cumulative clinical pregnancy rates in a population with endometriosis and a control group ( 23 ). Here, the live birth rate was significantly lower in the group of women with an AFC of ≤ 7 group than in those with an AFC > 7.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that age <35 years, infertility duration <5 years, secondary infertility, endometriosis fertility index (EFI) score and the use of ART were the predictive factors for postoperative pregnancy success ( 22 ). Advanced endometriosis has negative effect on the cumulative clinical pregnancy rate per oocyte retrieval cycle, and the AFC is an independent predictor of this ( 23 ). A recent study enrolling 485 patients with different stages of endometriosis undergoing their first IVF cycle concluded that female age, bilateral AFC and the number of embryos transferred were significant independent predictors of live birth ( 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…The impact of endometriosis on the reproductive outcome of patients undergoing IVF‐ET has been controversial 12–14 . Some previous study reported that the patients with advanced endometriosis had reduced clinical pregnancy rate of IVF 13 .…”
Section: Discussionmentioning
confidence: 99%